New perspectives in immunological diagnostics of coronary heart disease - S. I. Davydov; A. A. Tarasov; A. L. Emelyanova; M. A. Kiseleva; A. R. Babaeva (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the diagnostic value of immunological markers of endothelial dysfunction (ED) in various clinical variants of coronary heart disease (CHD). Material and methods. The study included 455 patients with various clinical variants of CHD. The control group (CG) included 70 individuals without clinical CHD symptoms. Solid-phase immunoenzymatic method was used for measuring the serum titres of Chlamydia pneumoniae (Cp), sulphated glycosamineglycanes (s-GAG), collagen (C), and hyaluronic acid (HA) antibodies. Results. In patients with acute coronary syndrome (ACS), mean titres of Cp, s-GAG, C, and HA antibodies were significantly higher than in patients with chronic CHD or CG participants. Among patients with myocardial infarction (MI), the levels of troponin I (TrI) and MB-creatine phosphokinase (MB-CK) significantly correlated with the titres of s-GAG and C antibodies, while the levels of C-reactive protein (CRP) were linked to the titres of C and HA antibodies. In ACS with ST segment elevation, the measurement of Cp, s-GAG, C, and HA antibodies was comparable to the measurement of CRP, TrI, or MB-CK activity, being significantly more sensitive than echocardiography (EchoCG). In non-ST ACS, immunological parameters were as sensitive as electrocardiography or CRP measurement, more reliable than MB-CK activity measurement or EchoCG, and slightly less reliable than TrI measurement. In unstable angina pectoris (UAP), immunological analysis was significantly more sensitive than the majority of the standard diagnostic methods. Conclusion. Pathogenetic mechanisms of ACS are closely related to the development of specific autoimmune reactions. The assessed immunological parameters could be used as objective markers of acute CHD variants.